Reconsidering the “MR Unsafe” breast tissue expander with magnetic infusion port: A case report and literature review - Rami Dibbs; Bozena Culo; Ravi Tandon; Hugo St. Hilaire; Frank G. Shellock; Frank H. Lau (Archives of Plastic Surgery, 2019)
Breast tissue expanders (TEs) with magnetic infusion ports are labeled “MR Unsafe.” Therefore, patients with these implants are typically prevented from undergoing magnetic resonance imaging (MRI). We report a patient with a total submuscular breast TE who inadvertently underwent an MRI exam. She subsequently developed expander exposure, requiring explantation and autologous reconstruction. The safety profile of TEs with magnetic ports and the use of MRI in patients with these implants is surprisingly controversial. Therefore, we present our case report, a systematic literature review, and propose procedural guidelines to help ensure the safety of patients with TEs with magnetic ports that need to undergo MRI exams.